Malassezia restricta Pneumonia in Solid Organ Transplant Recipients: First Report of Two Cases - Alessandra Mularoni; Elena Graziano; Alice Annalisa Medaglia; Barbara Buscemi; Taylor Eddens; Lavinia Martino; Daniele Di Carlo; Antonio Cascio; Pier Giulio Conaldi; Alessandro Bertani; Paolo Antonio Grossi (Journal of Fungi, 2021)
Emerging fungal infections are a major challenge in solid organ transplantation (SOT) and are associated with high morbidity and mortality. We report two cases of Malassezia restricta pneumonia in SOT recipients. Infections were diagnosed with molecular analysis and histology. Patients were treated with antifungal therapy and have fully recovered.